Macrophage infection with combinations of BCG mutants reduces induction of TNF-α, IL-6, IL-1β and increases IL-4. (March 2019) - Segura-Cerda, Cristian Alfredo; Aceves-Sánchez, Michel de Jesús; Pérez-Koldenkova, Vadim; Flores-Valdez, Mario Alberto
Abstract: Tuberculosis (TB) is the most prevalent infectious disease worldwide, with no fully effective vaccine yet available. Considering that BCG strains devoid of the BCG1416c or BCG1419c genes afforded protection in mice versus highly virulent M. tuberculosis challenge, or in chronic infection models compared to BCG, respectively, we hypothesized that a synergistic effect of these strains might occur and provide enhanced protection against TB. Herein, we evaluated this hypothesis throughout an experimental design approach, where different combinations of these strains were tested for their capacity to induce cytokines in vitro, compared to individual strains. Our results show that mixed-infection of murine macrophages using these strains significantly decreases induction of TNF-α, IL-1β, IL-6 but increases IL-4 induction compared with individual strains. These results suggest the existence of interaction effects during infection, which reduce induction of pro-inflammatory cytokines, even though individual intracellular replication is not altered when strains are combined. This is the first report of the evaluation of a potential whole-live combined vaccine against tuberculosis, which paradoxically seems to reduce production of pro-inflammatory cytokines while induces IL-4, leading us to further hypothesize that this combination might contribute as a therapeutic vaccine to reduce inflammation in severe TB cases.